2018
DOI: 10.4236/tel.2018.811127
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and Economic Growth: The Case of Emerging Economies

Abstract: The roles of institutional quality on economic growth are still heavily debated in the literature. This paper investigates the impacts of institutional quality on economic growth for 29 emerging economies over the 2002-2015 period by employing System Generalized Method of Moments (SGMM) estimators. We find the significant positive impacts of institutional quality on economic growth. The institutional quality impedes the positive effects of foreign direct investments (FDIs) and trade openness on economic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(66 citation statements)
references
References 35 publications
9
56
1
Order By: Relevance
“…A high level of inward capital flows also simulate the development of the financial sector while the domestic banking system can transform illiquid assets into liquid assets accessible although nationals may over-borrow abroad and over-lend domestically (Krugman, 1999). Even though inward FDI flows usually have a positive impact on the economic growth through a spillover effect (due to productivity, technological transfer and human capital), it is not necessary true in all cases (Huynh et al, 2020, Nguyen et al, 2018b, Nguyen et al 2018c). Samarina and Bezemer (2016) showed that domestic banking system in emerging economies does not have the ability to transform assets due to the lack of financial tools -Such situation significantly reduces the effect of inward FDI on credit volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A high level of inward capital flows also simulate the development of the financial sector while the domestic banking system can transform illiquid assets into liquid assets accessible although nationals may over-borrow abroad and over-lend domestically (Krugman, 1999). Even though inward FDI flows usually have a positive impact on the economic growth through a spillover effect (due to productivity, technological transfer and human capital), it is not necessary true in all cases (Huynh et al, 2020, Nguyen et al, 2018b, Nguyen et al 2018c). Samarina and Bezemer (2016) showed that domestic banking system in emerging economies does not have the ability to transform assets due to the lack of financial tools -Such situation significantly reduces the effect of inward FDI on credit volatility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, another important result that has been obtained in the results is that the GDP has significant along with positive impact on financial development of a country. These two aspects are very much related to each other and many studies in the past have confirmed this result (Chen & Lei, 2018;Nguyen, Su, & Nguyen, 2018;Rani & Kumar, 2019). As the GDP of a country increases, different sectors of the country get benefited financially from this increase in GDP and thus the FD is increased.…”
Section: Resultsmentioning
confidence: 73%
“…Sharma and Mitra (2019) argue that weak state institutions adversely affect certain economic segments and phenomena. Also, it stimulates unfair competition and favours policy-related individuals who expect to take a portion of the social and public property (Nguyen et al, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Sharma and Mitra (2019) argue that weak state institutions adversely affect certain economic segments and phenomena. Also, it stimulates unfair competition and favours policy-related individuals who expect to take a portion of the social and public property (Nguyen et al, 2018). So, while the economic cycle represents the economy's natural uctuations between periods, such as GDP growth, it is still important to discover the direct effects of privatisation on economic growth (Goldstein, 1997;Gray & Gray, 1996;Zhang, 2006).…”
Section: Hypothesis Developmentmentioning
confidence: 99%